Dimensions of Parenting and Their Relation to Emotional Intelligence in Emerging Adults - Ankita Dey; Agnimita Mitra (Journal of Psychology and Social Sciences, 2026)
During the critical stage of early adulthood, cultivating emotional intelligence-related abilities like social competence and emotional regulation may be useful for enhancing general well-being. The present study explored the relationship between parenting styles and emotional intelligence (EI) among emerging adults, with the primary objective of examining how different parenting approaches are related to the development of EI in individuals aged 19 to 25. A quantitative research design was employed, utilizing the Parental Authority Questionnaire (PAQ) by Buri (1991) and the Emotional Intelligence Scale by Dr. Arun Kr. Singh & Dr. Shruti Narain (2014). Data were collected from a sample of 100 college and university students. Pearson’s Product-Moment Correlation was computed using the SPSS-26 software. Overall, findings indicated no statistically significant correlation between general parenting styles and the emotional intelligence of emerging adults. However, in-depth analysis revealed that mothers' authoritative parenting style was comparatively more correlated with higher EI levels. Conversely, fathers' parenting styles showed minimal correlation, suggesting a limited paternal influence on the emotional development of their children in this sample. These results provide a potential importance of emotional presence and involvement in parenting. In particular, the data suggest that when a father is not consistently emotionally engaged or involved in everyday interactions, even if he adopts an authoritative style, his impact on the child's emotional development may be limited. The study contributes to the understanding of family dynamics and underscores the differentiated roles of mothers and fathers in shaping emotional intelligence during emerging adulthood.